Electrical and Mechanical Properties of Silicone Electrical Conductive Adhesives (ECAs) Filled Carbon Black Treated with 3-Aminotriethoxysilane at Elevated Temperature - Hasnol, Nurul Hazirah; Ahmad, Zuliahani; Sarip, Muhamad Naiman; Mohamad, Ahmad Faiza; Samsudin, Ahmad Salihin; Arief, Y.D (International Journal of Integrated Engineering, 2022)
In this study, different formulation of silicone filled carbon black electric conducting adhesive (ECAs) were successfully fabricated. Carbon black (CB) was treated with 3-aminotriethoxysilane to improve the surface adhesion by grafting of amide functional groups on the surface of the CB. Various loading of untreated and treated CB (0%,5%,10% and 15%) on silicone ECAs using film casting method were prepared and characterized. The characterization was performed on the conductive adhesive film by using Fourier Transform Infrared Spectroscopy (FTIR), hardness and tensile testing. While for the electrical property, electrochemical impedance spectroscopy (EIS) was investigated. The FTIR spectrums confirmed the surface modification of CB with 3-aminotriethoxysilane and amide functional groups was presence at 1549 cm-1, 1250.7 cm-1, 1126.6 cm-1, 976.16 cm-1 and 860.02 cm-1 corresponding to the N-H, SiO-H, Si-O-Si, C-N and C=C stretching vibrations of the amino groups (-R-NH3+) respectively. The conductivity of the ECAs was dependent on the CB loadings. As the CB loading increased, the conductivity of adhesive conductive film was increased up to 10% of CB loading and decreased when at 15% of CB loading. This is due to the gap distance of interparticle of silicone and CB is high. Whilst the tensile strength of the silicone filled CB increased with increasing of CB content both untreated and treated CB at 0.05954 MPa and 3.3027 MPa respectively. This is supported by hardness testing also showed the same trend with increment of CB loading, the hardness value also increased. The optimum value was found at 42 and 54 for untreated and treated CB respectively. The optimum formulation of electric conductivity was found at 10% loading of CB at 1.75E-08 ï—/cm. The conductivity of ECAs filled CB at elevated temperature exhibits increment trend of untreated/treated CB at temperature of 100 Â°C to 160 Â°C however decreased at 180 Â°C. It is believed that with increasing the temperature, the interparticle average distance increase due to the difference in the thermal expansion of silicone and carbon black. The utilization of treated CB in silicone ECAs improved the conductivity and mechanical properties giving way to a full potential of using CB as filler.